Awareness and Usage of E-CRM Tools & Techniques: A Study of Banking Industry in Punjab - Kaur, Jasveen; Kaur, Baljit (Gyan Management Journal, 2014)
In the fast dynamic economic environment, e-CRM technology has become a golden opportunity for the banking industry to accomplish the competitive-cum-customers strategies. The objective of this exploratory study has been to determine the relevance of tools and techniques of the e-CRM technology conceptually and to empirically examine the usage of these e-CRM tools and techniques among the bank users (customers) in the banking industry of India, more specifically in the Punjab state. It has been found that e-CRM tools and techniques help to provide potential benefits for banks and bank customers by using the technology-oriented systems. It has been concluded that e-CRM has enabled banking at the click of the mouse facilities in the changing scenario at the blink of an eye. E-CRM tools and techniques provide valuable inputs for developing services and facilities and retaining customers for the future.
Keywords: Banking Reforms; Techno-savvy Banks; e-CRM Tools and Techniques; Benefits; Customer Satisfaction and Competitive Advantage